Project-Based Learning on ESP: Students’ Perception of The Readiness to Work in The Tourism Industry - Purnawati, Maria; Sari, Nara (English Literature Department, Faculty of Economics, Law, and Humanities, 2023)
To respond to the demands of the world of work or industry that require graduates who have 21st century competencies, namely communication, collaboration, critical thinking, and creativity (4Cs). Students of the English Literature Study Program need to be equipped with these competencies through learning activities and learning models that support especially in the English for Tourism 1 course. One learning model that can help in developing 4C skills is Project-Based Learning (PjBL). With the application of the PjBL model, students can build collaboration, communication, critical thinking and creativity skills. This study aims to describe the implementation of project-based learning (PjBL) as a reinforcement for students to be ready to work in the tourism industry. In addition, it is also necessary to know students' perceptions during the implementation of PjBL towards their readiness for a career in the tourism industry. This research used qualitative descriptive approach. The subjects of this research were 20 students in the English for Tourism I course at the English Literature Study Program, Faculty of Language and Literature, Universitas PGRI Kanjuruhan Malang. The research subjects worked in groups to create a tour package project. The implementation of the PjBL learning model was observed using observation sheets, and questionnaires to explore data on students' perceptions of the implementation of PjBL on their readiness to work in the tourism industry. The result of this study showed that students had positive perceptions of the implementation of project-based learning. Most of the students agree that the implementation of project-based learning improves their communication, collaboration, critical thinking, and creativity. Moreover, after doing the project, 45% of the participant strongly agreed, and 40% agreed that the implementation of PjBL improved their readiness to work in the tourism industry.